2019
DOI: 10.3390/rs11182156
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Height and Aboveground Biomass of Mangrove Forests on Hainan Island Using UAV-LiDAR Sampling

Abstract: Hainan Island is the second-largest island in China and has the most species-diverse mangrove forests in the country. To date, the height and aboveground ground biomass (AGB) of the mangrove forests on Hainan Island are unknown, partly as a result of the challenges faced during extensive field sampling in mangrove habitats (intertidal mudflats inundated by periodic seawater). Therefore, this study used a low-cost UAV-LiDAR (light detection and ranging sensor mounted on an unmanned aerial vehicle) system as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 77 publications
(105 reference statements)
2
30
1
Order By: Relevance
“…The variable importance results in Figure 5 show that the SWIR bands 11 and 12 of the S-2 sensor play an important role in mangrove AGB retrieval in the study area. This finding is consistent with recent studies reported by Wang, et al [89]. In addition, two vegetation red-edge bands (bands 5 and 6) were found to be sensitive to mangrove AGB in the biosphere reserve.…”
Section: Discussionsupporting
confidence: 93%
“…The variable importance results in Figure 5 show that the SWIR bands 11 and 12 of the S-2 sensor play an important role in mangrove AGB retrieval in the study area. This finding is consistent with recent studies reported by Wang, et al [89]. In addition, two vegetation red-edge bands (bands 5 and 6) were found to be sensitive to mangrove AGB in the biosphere reserve.…”
Section: Discussionsupporting
confidence: 93%
“…However, these approaches are disadvantaged by high cost and site-selection biases [15]. Cost-effective and accurate retrieval techniques for mangrove AGB in tropical and semi-tropical areas would provide baseline data for the monitoring, reporting, and verification schemes adopted in climate-change mitigation strategies, such as Blue Carbon projects and the United Nations' Reducing Emissions from Deforestation and Forest Degradation (REDD+) program in the tropics [16].In recent years, mangrove AGBs have been increasingly mapped using earth observation (EO) data collected by optical sensors [17][18][19], synthetic aperture radar (SAR) data [13,20,21], airborne LiDAR [22,23], and LiDAR data acquired form unmanned aerial vehicles (UAV) [24,25]. A few attempts combined the data of multispectral and SAR sensors for mangrove AGB retrieval in tropical regions.…”
mentioning
confidence: 99%
“…Meanwhile, numerous EO datasets have been compiled from optical, SAR, and LiDAR data. These data are commonly retrieved from non-parametric regression techniques such as the random forest regression (RFR) algorithm [17,25,27], artificial neuron networks (ANN) [26], and support vector regression (SVR) [28,29]. Recently, gradient boosting decision trees (GBDT) effectively solved regression problems such as evaporation prediction [30] and oil price estimation [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methodologies based on high-resolution light detection and ranging (LiDAR) have also been used in this context (Sankey et al 2017;Guo et al 2017;Cao et al 2019;Almeida et al 2019), enabling high-density point clouds to be generated from the highresolution RPAS images and showing advantages over those heretofore commonly collected by larger, manned aircraft as LiDAR platforms (Sačkov et al 2016). Moreover, this type of study has enabled advances regarding the detection of individual trees, which is another widely reported application, capable of providing highly accurate and spatially detailed information about the forest attributes across a forested landscape (Mohan et al 2017;Balsi et al 2018;Wu et al 2019;Wang et al 2019). Liu et al (2018), studying a ginkgo (Ginkgo biloba L.) plantation, evaluated estimates of parameters such as diameter at breast height, Lorey's mean height, stem density, basal area, volume, and aboveground biomass.…”
Section: Forest Inventory and Estimation Of Dendrometric Parametersmentioning
confidence: 99%